Rural Women Socialization and its Relationship with Family Development in two Villages in Kafr El-Sheikh Governorate - Hegazy, Hassan Mohammed Al-Nabawi; Hassan, Noha Al-Zahi; El-Diasty, Hossam Mohammed Hasan (Journal of Humanities & Social Sciences, 2022)
This research aimed to identify: rural women’s practices level in developing thier families socially and economical in Kafr El- Sheikh Governorate, Rural women’s main sources of knowledge for family development, the level of socialization methods that rural women have been exposed to, and the relationship between the degree of socialization methods that rural women have been exposed to and the degree of family development in Kafr El- Sheikh Governorate, The study used the descriptive analytical method, The sample size was 150 individuals. Research data were collected by using personal interviewing questionnaire, and the results are presented by using frequencies, percentages, mean, and the Person’s simple correlation coefficients. The study showed the following: More than 60% of the rural women surveyed their level of practice in family development was high. while 39.3% of them had a medium level of practice, the family as a source of knowledge for rural women to develop their families outperformed schools and places of worship according to the average frequency, more than 83% of the total respondents were exposed to a medium level of traditional methods of socialization, while more than 57% of them were exposed to a high level of non-traditional methods of socialization, and there is a significant positive relationship between each of the non-traditional socialization methods and each of the axes: saving money, developing positive children’s values and practices, rationalizing food consumption, preserving the environment, and the overall practices of rural women for family development. the study recommended increasing the role of the media in spreading awareness of modern socialization methods and integrating the topic of modern socialization and knowledge of rural family development within the advocacy discourse for places of worship, and working for the school to play a greater role in spreading knowledge of family development.